The degree of availability of children's literature standards in my language course for the early grades in KSA - Al-Nadawy, Mutlaq Yaessh (Journal of Curriculum and Teaching Methodology, 2022)
The current research aimed to prepare a list of children’s literature standards that need to be available in my language course for the early grades and measure their availability, following the descriptive analytical approach. The tool used was a content analysis card that included children’s literature standards and indicators. Early years), in the Kingdom of Saudi Arabia, and the research revealed that the criteria for the linguistic field were highly available in my language book with an arithmetic average for the first grade (2.58), the second (2.58) and the third primary (2.75).As for the standards of the educational field, they were found to a high degree in my language book, with an arithmetic average for the first grade (2.54), the second (2.67) and the third primary (2.77).In light of the results of the research, the researcher recommended several recommendations, the most important of which is the necessity of conducting an analytical study of the prose texts included in my beautiful language books for the top three grades.
Keywords: Children's literature; my language course; early grades